HUBUNGAN KEBIASAAN MEROKOK DENGAN STATUS GINGIVA PADA REMAJA USIA 15-19 TAHUN - Manibuy, Katarina D.; Pangemanan, Damajanty H. C.; Siagian, Krista V. (e-GiGi, 2015)
Abstract:Currently, smokers in Indonesia have already included teenagers. Adolescent phase is particularly vulnerable to try new things with the purpose of identity searching, one of which is through smoking. Smoking does not only cause a systemic effect on the body, but can also cause pathologic conditions in the oral cavity such as gingivitis. Accumulation of heat and combustion products of cigarettes can affect the response of gingival inflammation. The objective of this study was to determine the relation between smoking habits based on the amount and duration of smoking cigarettes with gingival status in adolescents aged 15-19 years in Tuminting district.This research was descriptive analytic with cross sectional approach. The population was all adolescents aged 15-19 years in Tuminting district. A sample of 99 adolescents was taken using proportional random sampling. The data were collected using questionnaires and checks on gingival status by gingival index.The research findings show that as many as 49 adolescents (49.5%) had a mild smoking habit based on the number of cigarettes (1-4 cigarettes/day), 39 adolescents (39.4%) had a heavy smoking habit by smoking duration (>2 years) and 70 adolescents (70.7%) had mild gingival status. Chi-square test results show no significant relation between smoking habits based on the amount of cigarettes smoked and gingival status (p>0.05), but smoking habits based on the duration of smoking relate to gingival status (p<0.05).Keywords: smoking habit, gingival status, adolescentsAbstrak:Saat ini, perokok di Indonesia sudah mencakup ke kalangan remaja. Fase remaja sangat rentan untuk mencoba hal-hal baru dengan tujuan untuk pencarian jati dirinya, salah satunya yaitu dengan caramerokok. Kebiasaan merokok tidak hanya menimbulkan efek sistemik pada tubuh, tetapi juga dapat menimbulkan kondisi patologis di rongga mulut, salah satunya yaitu gingivitis.Panas dan akumulasi produk hasil pembakaran rokok dapat memengaruhi respon inflamasi gingiva. Tujuan penelitian ini untuk mengetahui hubungan kebiasaan merokok berdasarkan jumlah rokok dan lama merokok dengan status gingiva pada remaja usia 15-19 tahun di kecamatan Tuminting.Penelitian ini merupakan penelitian deskriptif analitik dengan pendekatan cross sectional. Populasi penelitian ialah seluruh remaja usia 15-19 tahun di kecamatan Tuminting. Jumlah sampel 99 orang diambil dengan caraproportional random sampling. Pengumpulan data menggunakan kuesioner dan pemeriksaan status gingiva berdasarkan indeks gingiva.Hasil penelitian ini menunjukkan bahwa sebanyak 49 orang (49,5%) memiliki kebiasaan merokok ringan berdasarkan jumlah rokok (1-4 batang rokok/hari), 39 orang (39,4%) memiliki kebiasaan merokok berat berdasarkan lama merokok (>2 tahun), 70 orang (70,7%) yang memiliki status gingiva ringan. Hasil uji chi-sqaure menunjukkan bahwa tidak terdapat hubungan antara kebiasaan merokok berdasarkan jumlah rokok dengan status gingiva (p>0,05) namun kebiasaan merokok berdasarkan lama merokok berhubungan dengan status gingiva ((p<0,05).Kata kunci: kebiasaan merokok, status gingiva, remaja